MSMEs Go Green Pays Less: Efficiency Strategies to Minimize the Impact of Carbon Tax - Thalib, Maryati Kadir; Lomagio, Afriana; Sholehah, Nur Lazimatul Hilma (Gorontalo Accounting Journal, 2026)
This study examines the understanding, perceptions, readiness, and adaptation strategies of Micro, Small, and Medium Enterprises (MSMEs) in Gorontalo, Indonesia, toward carbon tax policies. MSMEs remain highly dependent on fossil-based energy, while their knowledge and capacity to adapt to environmental fiscal instruments are still limited. This study employed a descriptive qualitative approach using in-depth interviews with purposively selected food-sector MSMEs, supported by policy documents, official reports, and relevant literature. Data were analyzed through thematic analysis focusing on understanding, readiness, perceptions, challenges, and adaptation strategies. The findings indicate that most MSMEs have limited knowledge of carbon tax mechanisms and generally perceive the policy as an additional financial burden. Although negative perceptions and uncertainty are common, some business actors emphasize the importance of fairness and transparency in policy implementation. Only a small proportion of MSMEs demonstrate readiness to adapt when supported by government incentives, green technologies, and technical assistance. Key challenges include limited technical knowledge, financial constraints, restricted access to environmentally friendly technology, and regulatory complexity. Existing adaptation efforts are mainly limited to energy-saving practices and reducing plastic packaging. The study concludes that successful carbon tax implementation among MSMEs requires inclusive government support to facilitate a fair and sustainable transition toward a green economy.